IMPLEMENTASI KEBIJAKAN RETRIBUSI PARKIR GUNA MENINGKATKAN PENDAPATAN ASLI DAERAH KOTA PEKALONGAN - Ardiansyah, Roy; Sundarso, Sundarso; Yuniningsih, Tri (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Parking is part of a sub-system of the implementation of the road freight traffic carried by local governments, in order to improve the organization of the society in the field of environmental management, order and smooth flow of traffic as well as a source of revenue (PAD). Pekalongan city parking retribution policy refers to the Regional Regulation No. 21 of 2011 on Service Fees for parking. Has the objective to increase transparency and accountability, and to support the process of monitoring the implementation of parking retribution. These objectives can be achieved through the implementation of the views of the appropriateness of the policy, the accuracy of the executor, the target accuracy, precision and accuracy of the process environment. Parking Retribution Policy Implementation process in achieving the objectives are factors inhibiting and supporting factors. But in its application in the field face many obstacles that the implementation of parking charges less walking is not optimal. This research was conducted with descriptive qualitative research methodology that aims to identify and analyze the implementation of parking charges implementation of the results of this study is not optimal due to the presence of obstacle factor the resource factor in the number of staff employees and the bureaucratic structure of the relevant Department. Parking attendants themselves are also often delayed depositing retribution results due to use such proceeds to their daily lives. In addition, public opinion against the parking retribution to be indifferent to never ask for proof of parking tickets after paying. Based on the results of these studies recommended to be done to increase supervision of the implementation of parking retribution. This is for the implementation of parking retribution to the maximum